ADULT PATIENTS' LABORATORY DIAGNOSIS OF URINARY TRACT INFECTIONS - Abdualwahab Mohamed Madkali , Abdulaziz Dakhil Saad Alshahrani , Khalid Moadi Assiri , Ali Abdullah Mohmmed Alkhathami , Hajar Ali Alhasani , Fareah Ali Abutalib Alhassani , Mariam Mustafa Bbutalib Alhasani,; Hamad Ali Ali Alhayli , Mohammed Ahmed Ibrahim Alsahabi , Abdulaziz Fayez Almoslei , Asrar Hasan Algubishi, (Chelonian Research Foundation, 2022)
One of the most frequent bacterial infections, urinary tract infections (UTIs) make up a large portion of the workload in clinical microbiology labs. The most common cause of urinary tract infections (UTIs) is still enteric bacteria, especially Escherichia coli, albeit the location of these pathogens is shifting. The rise of resistance to certain antimicrobial agents—most notably, E's resistance to trimethoprim-sulfamethoxazole—is more significant. Coli. A limited number of assays are used by doctors to differentiate UTIs from other infections with comparable clinical presentations; however, none of these tests have sufficient sensitivity or specificity when used alone. Urinalysis is a valuable diagnostic test mostly for ruling out bacteriuria. Urine culture may not be required for the examination of outpatients with simple UTIs, but it is required for inpatients with UTIs as well as for outpatients with severe UTIs, recurring UTIs, and treatment failures. keywords: Urinary tract infections (UTIs), Laboratory diagnosis, Adult patients, Antimicrobial resistance